Proposed Model of Coast Guard Enhancing Maritime Security and Safety in the Republic of Slovenia - Twrdy, Elen; Androjna, Andrej; Pavliha, Marko (Promet - Traffic&Transportation, 2014)
In the modern world, the sea is one of the most important resources for the economy and welfare of the country that has access to it and so is the sense of security. Meeting today’s security challenges requires a wide spectrum of civil and military instruments. It calls for regular coordination, consultation and interaction among all actors involved, and it requires a national multifunctional Structure. The paper presents the search for new systematic forms to ensure adequate maritime security and safety at sea. Based on the research on successfully organized similar foreign institutions in relation to the national security institutions in the maritime domain the Coast Guard model of the Republic of Slovenia has been designed. The model could significantly improve the level of efficiency and consistency of national authorities in the area of control, security and safety of the territorial sea and rationalize expenditures. Implementing the proposed model and placing it in the national security and defence system, is a challenge and also a need.